Factors Related To Compliance With The Use Of Personal Protective Equipment (PPE) Against Employees At Pt.Mas Batang Toru Mine 2023 - Fauziah Gusvita Syarah Harahap (CV. AFDIFAL MAJU BERKAH, 2023)
Indonesia is a country that still has a high number of work accidents, especially well-known companies . This is supported by data from the Ministry of manpower which noted an increasing trend in the number of work accidents in Indonesia which has continued to increase in recent years. in 2022, there have been 157,313 cases of work accidents, or an increase compared to work accident cases that occurred in 2019 of 154 thousand cases. One of the main causes of work accidents is the low awareness of the importance of K3 compliance and non-compliance in the use of personal protective equipment in the industry. The design of this study uses an analytical survey with a cross sectional approach. the sample in this study as many as 50 workers of PT Tambang Mas Batang Tou. Statistical tests used are chi square test and logistic regression. The results showed that of the total respondents 51.0% aged 23-38 years, 32.0% have high school education, 76.0% have worked for 15-20 years. The results of bivariate analysis using chisquare showed that knowledge (p=.000), attitude (p=.000), the availability of PPE (p=.000), regulation (p=.000) and control (p=.000). From the multivariate analysis of the factors that are very influential in this study is the availability of PPE with a value of OR is 745.00 means that respondents whose PPE availability is less than 745 times have the opportunity to cause non-compliance respondents in the use of PPE. From the results of this study is expected to management of PT.Mas Batang Toru mine to be able to further maintain promotive efforts towards the use of personal protective equipment in order to influence the knowledge and attitude of the workforce to wear complete personal protective equipment and maintain the condition of personal protective equipment in good condition before the replacement period by adding demonstration methods for the use and maintenance of personal protective equipment during safety talk.